2014
DOI: 10.1139/apnm-2013-0287
|View full text |Cite
|
Sign up to set email alerts
|

A pilot program for physical exercise promotion in adults with type 1 diabetes: the PEP-1 program

Abstract: [Purpose] The aim of this study was to compare age-related differences in balance and anthropometric posture measurements of the foot and to determine any relationship between them. [Subjects and Methods] Sixty-eight older and 42 younger adults participated in this study. Foot posture was tested for four domains: 1) hallux flexion and extension range of motion using a goniometer, 2) navicular height and 3) length of the foot using a pachymeter, and 4) footprint (width of forefoot, arch index and hallux valgus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Data from other age groups may also be informative. Group interventions including weekly MVPA and DSME sessions for adults and young children (9‐11 years) with type 1 diabetes did not increase MVPA outside the group sessions. Taken together, these data and ours indicate a personalized goal‐setting approach may be more effective at promoting habitual MVPA for type 1 diabetes …”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Data from other age groups may also be informative. Group interventions including weekly MVPA and DSME sessions for adults and young children (9‐11 years) with type 1 diabetes did not increase MVPA outside the group sessions. Taken together, these data and ours indicate a personalized goal‐setting approach may be more effective at promoting habitual MVPA for type 1 diabetes …”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, participants in the previous group intervention for adults with type 1 diabetes improved peak oxygen uptake and systolic blood pressure compared with non‐participating controls . It is possible that even group interventions unable to promote MVPA more than once per week could still gain from this modest MVPA dose some positive impact on clinically important outcomes for type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pilot program for physical exercise promotion in adults with Type 1 diabetes: the PEP-1 program, the only other unsupervised exercise programme for adults with Type 1 diabetes, activity was not increased [20]. In four studies of unsupervised exercise studies in adolescents and/or children, two showed an increased activity at 3-4 months and two did not [21].…”
Section: Discussionmentioning
confidence: 97%
“…Any form of exercise could be undertaken and exercise could be accumulated throughout the day in bouts of at least 10 min. Participants met with the nurse for 20 min to discuss their exercise levels at 2,4,8,12,16,20,30, 36 and 42 weeks as specified in the protocol. Using a protocol similar to this, we have shown that we can increase and maintain exercise levels in a variety of patients with chronic diseases including patients with newly diagnosed Type 2 diabetes [8][9][10].…”
Section: Methodsmentioning
confidence: 99%